STRATEGI MENGATASI TANTANGAN MENGIMPLEMENTASIKAN FORMULASI STRATEGI DALAM LEMBAGA PENDIDIKAN - Rida Restu Restalillah; Dea Prastia; Trisna Mutiara; Linardo Pratama (CV. Adiba Aisha Amira, 2025)
This study aims to analyze strategies to overcome the challenges of implementing strategy formulation in educational institutions facing resource limitations. This study uses a literature review method by reviewing various scientific sources such as articles, journals, and books relevant to the research topic. The results indicate that the main challenge in implementing strategy formulation in educational institutions is the mismatch between limited resources and overly ambitious institutional goals. To overcome this, it is necessary to implement a strategy formulation based on the reality of resources through steps such as educational resource audits, strategic priority setting, and ongoing monitoring and evaluation mechanisms. With this approach, educational institutions can develop policies that are more adaptive, realistic, and oriented towards improving the quality of learning despite resource limitations.